A study of the use of the definite article ‘the’ in academic essays by Sri Lankan undergraduates at the Department of English in the University of Colombo - Fernando, Siromi (My University, 2008)
In this paper, a report is made of a study of the use of the definite article ‘the’ in academic essays by Sri Lankan undergraduates at the Department of English, University of Colombo. This study of limited focus has relation to a larger issue, the use of ‘the’ in English academic writing of Sri Lankans with a relatively high level of English proficiency. The data for this study is drawn from the academic essays of twenty-one undergraduates following English as a subject, i.e. persons of a relatively high level of English proficiency. Fourteen per cent of the undergraduates in the study had no problems with the use of ‘the’ in academic writing. They had good proficiency in Sri Lankan English. The other 86 % made 283 errors, although these were much smaller in proportion to instances of correct use, both of definite and indefinite articles. The English of the other 86% ranged from good proficiency, to moderate or lesser levels of good proficiency. It had already been predicted that certain categories in the use of ‘the’ would not occur in academic writing, as these categories are more confined to informal, colloquial use. As predicted, no instances of these categories were found. Of the other categories, the errors were of two main types, the omission of the definite article, and the incorrect addition of the definite article. The omission is, by far, the more recurrent, totalling about 51 % of all errors. However a considerable proportion of errors in incorrect addition, about 22 %, was also found. The category of Cataphoric reference accounted for the main source of error, totalling about 38 %. It was also found that about 50 % of errors were limited to five of the undergraduates, although the other 50 % was distributed among the other13 who made errors. The study demonstrated that ignorance of rules pertaining to the use of ‘the’ and lack of correction of written work, or correction without explanation of reasons for errors contributed to problems regarding the use of ‘the’ in this study. Examination of the difference between English and the Sri Lankan languages in expressing concepts like definiteness did not come within the scope of this study, but it was suggested that research on this issue was necessary. It was also suggested that the difficulties in the use of ‘the’ can be effectively dealt with through discussion and systematic teaching of the rules. In addition, the categories that led to a large numbers of errors in the use of ‘the’, like cataphoric reference, should be emphasized in teaching.